2011
DOI: 10.1093/ecam/neq019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Cerebroprotective Effect of Medicago sativa Linn. against Ischemia and Reperfusion Insult

Abstract: Antioxidants have been the focus of studies for developing neuroprotective agents to be used in the therapy for stroke, which is an acute and progressive neurodegenerative disorder. Medicago sativa (MS) has a long tradition of use as ayurvedic and homoeopathic medicine in central nervous system disorders. The plant has been reported to have antioxidant, anti-inflammatory and antidiabetic effects. Therefore, the present study was designed to investigate the neuroprotective effect of methanol extract of MS on is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Arabian-type polysaccharide (GBW) extracted from Ginkgo biloba, polyphenols from a variety of foods, and Sophora alopecuroides extract oxidized alkaloids all have antioxidant effects on cerebral ischemia in animals (Alfieri et al, 2013;Yang et al, 2013Yang et al, , 2019Chu et al, 2019;Han et al, 2019). In a mouse model of CIRI, it was demonstrated that a purpura extract can significantly reduce infarct size, restore the activities of antioxidants such as SOD and GSH, and decrease pro-oxidase enzyme activity by xanthine oxidase (Bora and Sharma, 2011). The protective effect of resveratrol on CIRI in mice is also related to its antioxidant properties (Dou et al, 2019).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Arabian-type polysaccharide (GBW) extracted from Ginkgo biloba, polyphenols from a variety of foods, and Sophora alopecuroides extract oxidized alkaloids all have antioxidant effects on cerebral ischemia in animals (Alfieri et al, 2013;Yang et al, 2013Yang et al, , 2019Chu et al, 2019;Han et al, 2019). In a mouse model of CIRI, it was demonstrated that a purpura extract can significantly reduce infarct size, restore the activities of antioxidants such as SOD and GSH, and decrease pro-oxidase enzyme activity by xanthine oxidase (Bora and Sharma, 2011). The protective effect of resveratrol on CIRI in mice is also related to its antioxidant properties (Dou et al, 2019).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…A number of antioxidant enzymes are responsible for the removal of excess ROS in living organism. Among these, SOD is the most crucial enzymes in the cellular antioxidant system [36]. Furthermore, as an important product of lipid peroxidation, MDA also indirectly reflects the production of intracellular ROS [23].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, M. sativa has pharmacological effects of improving memory and relieving central nervous system diseases (Bora & Sharma, ; Rafinska, Pomastowski, Wrona, Gorecki, & Buszewski, ). Studies on mice confirmed that M. sativa acted as neuroprotective agent (Bora & Sharma, ; Rafinska et al, ). The literature reviews have indicated that oleanane triterpene saponins are the main components isolated from M. sativa (Gholami, Geyter, Pollier, Goormachtig, & Goossens, ; Ma et al, ; Rafinska et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the world, M. sativa is widely consumed as an excellent pasture for animals and a nutritious vegetable for humans in the form of salads, tortillas, puddings, soups, and casseroles (Cornara, Xiao, & Burlando, 2016;Martínez et al, 2016). Traditionally, M. sativa has pharmacological effects of improving memory and relieving central nervous system diseases (Bora & Sharma, 2011;Rafinska, Pomastowski, Wrona, Gorecki, & Buszewski, 2016). Studies on mice confirmed that M. sativa acted as neuroprotective agent (Bora & Sharma, 2011;Rafinska et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation